Picture Book as Wayfinding Intervention: A Critical Visual Analysis of Zoë Learns Healthcare Signs for Multilingual Users in Southern Nigeria - Stewart, Ashley; Inyang, Etiido (Universitas Ciputra, 2026)
Multilingual users of primary health centres in Nigeria face a significant but under-researched wayfinding challenge: institutional signage systems encoded in English and internationally standardised iconography that carry no bridge to the indigenous languages and cultural frameworks of their users. This study addresses that gap by critically analysing the picture book Zoë Learns Healthcare Signs (Stewart, 2025)—a purpose-designed visual communication artefact that deploys the conventions of the picture book genre to build wayfinding literacy among multilingual communities in Rivers State, Nigeria. Drawing on the Critical Picture Book Literacy (CPBL) framework of Stewart and Koopmans (2025), multimodal discourse analysis, and postcolonial design theory, the study evaluates how illustrator agency, identity representation, and unconscious bias operate within the book's visual text, and how its semiotic strategies bridge international wayfinding iconography with local linguistic knowledge. The analysis finds that the book makes three substantive design contributions: it constructs a culturally specific BIPOC child protagonist who repositions marginalised communities as knowing navigators; it pairs international wayfinding signs with Igbo and Ijaw equivalents, creating a multilingual bridge strategy without precedent in Nigerian healthcare design; and it deploys an enhancement mode of image-text interaction that faithfully replicates the semiotic challenge users face in actual healthcare environments. The study also identifies design limitations—typographic language hierarchy, inconsistent multilingual coverage, and a counterpoint safety-signs spread—and develops concrete, actionable recommendations for future iterations. By demonstrating how picture book design can function as a pre-emptive, community-embedded wayfinding literacy intervention, this study contributes an original framework applicable to inclusive health communication design in multilingual contexts across the Global South.